A pastoral da juventude em Goiânia: trajetória, experiência e atuação - Duarte, José Fernando (2019)
This dissertation is linked to the research line "Identity, Traditions and Territoriality". The purpose of this work is The Youth Pastoral of Brazil, which was instituted as a social movement of the Catholic Church, with an action directed to the youth. The objective was to delineate, from a historical perspective, how the Youth Pastoral of Brazil, from its directives and social representations, has been acting since the 1970s, in the production of protagonism among the young people of Goiânia. For that, the senses deposited in this category "protagonism" were analyzed. It had been observed that the YPB had direct influences from the General Catholic or Brazilian Actions, as well as on the Specialized, the Second Vatican Council, the See-Judge-Act Method, the Triennial Plans (1995, 1998, 2001, 2004, 2007), the Episcopal Latin American Medellín (1968), Puebla (1979), Santo Domingo (1992) and Aparecida (2007), in addition to Liberation Theology and Pedagogy of the Oppressed. The model of youth that the YPB intends to form was analyzed, observing the contents, social representations and methods used for this formation (integral formation). This model is called by the YPB as a "protagonist", a model that corresponds to a young person who possesses particularities of a subject, characterizing them as modern but with the potential to develop themselves within the movement and in a collective way. Although the YPB reifies the principles established institutionally by the Catholic hierarchy, it has its own characteristics that can go against such principles, which differentiates it from other catholic movements. The main characteristics of this young person model are: identity, autonomy, criticality, social participation and commitment to the collective.